CONFLICT IN KEVIN KWAN'S NOVEL CRAZY RICH ASIANS - Setiawati Anggraini; Asnani Asnani (JOURNAL OF LANGUAGE, 2023)
The study aims to describe the kinds of conflict and also the factors causing conflict in Kevin Kwan's novel Crazy Rich Asians. It only focuses on kinds of conflict and factors causing conflict in selected characters of the novel. This study used a qualitative method. The data were analyzed descriptively. The data in this study were collected from the novel Crazy Rich Asians by Kevin Kwan. The data were taken by reading and marking words and phrases from the novel, which are related to the study. The data were analyzed from the novel based on the theory and statement of the problem to be analyzed. The results of the analysis obtained from this study have two conclusions. First, the types of conflicts in the novel Crazy Rich Asians, namely internal and external conflict are found in several characters in the novel. Second, the factors that may cause conflict in the novel Crazy Rich Asians are causative factors. These factors are differences between individuals, cultural differences, and differences in interests. The results of this study are expected to provide benefits, understanding, and knowledge in analyzing conflict in a literary work in the form of a novel. The results of this study are also expected to be used as a reference for further research.